Kajian Keamanan Asap Cair Tempurung Kelapa untuk Produk Pangan - Slamet Budijanto; Rokhani Hasbullah; Sulusi Prabawati; Setiadjit Setiadjit; Sukarno Sukarno; Ita Zuraida (Institut Pertanian Bogor, 2008)
The objective of this research was to study the food safety od coconut shell liquid smoke for food products by acute toxicity test and identification of volatile compounds by means of Gas Chromatography- Mass Spectroscopy (GC-MS).Keyword: acute tixicity, coconut shell liquid smok, food safety, GC-MS, volatile compound